2008
DOI: 10.1128/mcb.00443-07
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Expression of β1 Integrin Is Required for Embryonic Vascular Patterning and Postnatal Vascular Remodeling

Abstract: The largest subgroup of integrins is that containing the ␤1 subunit. ␤1 integrins have been implicated in a wide array of biological processes ranging from adhesion to cell growth, organogenesis, and mechanotransduction. Global deletion of ␤1 integrin expression results in embryonic death at ca. embryonic day 5 (E5), a developmental time point too early to determine the effects of this integrin on vascular development. To elucidate the specific role of ␤1 integrin in the vasculature, we conditionally deleted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
81
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(90 citation statements)
references
References 39 publications
9
81
0
Order By: Relevance
“…Also of interest is that inhibition of ␣5␤1 integrin ligation increases PKA activation and may be an important mechanism whereby agents that alter intregrin function can inhibit angiogenesis (27). Recently we showed that endothelial cell-specific loss of the ␤1 integrin causes embryonic lethality and profound abnormalities in vascular development (28). It is interesting to consider that a PKA-mediated final common pathway may be involved in the vascular effects of Ucn2 and of altered integrin function.…”
Section: Discussionmentioning
confidence: 99%
“…Also of interest is that inhibition of ␣5␤1 integrin ligation increases PKA activation and may be an important mechanism whereby agents that alter intregrin function can inhibit angiogenesis (27). Recently we showed that endothelial cell-specific loss of the ␤1 integrin causes embryonic lethality and profound abnormalities in vascular development (28). It is interesting to consider that a PKA-mediated final common pathway may be involved in the vascular effects of Ucn2 and of altered integrin function.…”
Section: Discussionmentioning
confidence: 99%
“…Illustrations were prepared by O. Karengina based on an image of a mouse embryo at E13.5. (Furuta, 1995;Ilic et al, 2003) Vinculin Focal adhesions Total Death by E10, with embryos displaying 30-40% reduction in size, lack of midline fusion of the rostral neural tube and developmental defects in heart, somites and limbs (Xu et al, 1998) Zyxin Focal adhesions Total Viable, fertile, no obvious abnormalities (Hoffman et al, 2003) α4 integrin Integrins Total Embryonic lethality, defects in placenta and vascular system, cardiac hemmorhages (Yang et al, 1995) αv integrin Integrins Total Partial embryonic lethality, intracerebral and intestinal hemorrhages and cleft palates (Bader et al, 1998) α5 integrin Integrins Total Embryonic lethal and E10-11 with migration-type defects in posterior trunk and yolk sac mesodermal structures (Yang et al, 1993) Lei et al, 2008;Tanjore, 2008) Total Death shortly after implantation (Fassler and Meyer, 1995) In vitro studies of cells from knockout mice…”
Section: Note On Nomenclaturementioning
confidence: 99%
“…45 This involves the polarity gene Par3 which is down regulated in b1-deficient endothelial cells and animals lacking endothelial b1 die at E9.5 and 10. 46 Recently, Barry and colleagues showed the importance of VE-cadherin and the small GTPase Cdc42 in opening the vascular lumen. 47 Hence, b1-integrins may be directly or indirecty linked to VEcadherin during vessel development.…”
Section: Introductionmentioning
confidence: 99%